Evaluating the Sustainable Architecture Indicators in Tabriz Grand Bazar - Sadaf Tabatabaee; Ayda Rastiemadabadi (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2019)
The present study evaluates the sustainable architecture indicators of human relation with contemporaries in the Tabriz Grand Bazar and analyzes how the priorities of these indicators are implemented in this bazar. To achieve this goal, qualitative content analysis method is used. The data gathering tools used in this research is documentary and library studies and field studies in the form of questionnaires and observation. In this regard, at first, the sustainable architecture indicators are extracted based on international sustainable evaluation systems, such as LEED. In the second step, after validating the indicators, the audience's understanding of finalized indicators is evaluated. In order to achieve this goal, the quantitative data obtained through the completion of 320 questionnaires were analyzed using linear regression analysis in SPSS software. The results show that more than 85% of the indicators of human relation with contemporaries have a high impact on the realization of sustainable architecture. Thus, it can be said that the realization of the sustainability in Tabriz Grand Bazar is clearly understood by the audience, furthermore the public involvement and of vitality of the bazar spaces have the highest influence on the audience's understanding of sustainability in the Bazaar.